2020
DOI: 10.1177/1077546320957533
|View full text |Cite
|
Sign up to set email alerts
|

Active vibration control in human forearm model using paired piezoelectric sensor and actuator

Abstract: An active vibration control system to monitor and suppress the human forearm tremor is proposed in this article. The forearm is modelled as a uniform flexible continuous beam supported by a pin joint and a rotational spring at one end, whereas the other end is free. The beam is covered with a layer of piezoelectric sensor on its top surface and a layer of piezoelectric actuator on its bottom surface to form a control system, through which a closed-loop active control paradigm is implemented for tremor suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Similarly, using various motors or pumps to attenuate tremors in different directions is a challenge that is addressed using the MMS mechanism [56]. Furthermore, using rigid parts for wearable devices is a disadvantage that is overcome by utilizing soft actuators [58,60].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, using various motors or pumps to attenuate tremors in different directions is a challenge that is addressed using the MMS mechanism [56]. Furthermore, using rigid parts for wearable devices is a disadvantage that is overcome by utilizing soft actuators [58,60].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Hosseini et al designed a hand suppressor (active) with piezoelectric actuators and sensors on the top and bottom side of the arm [58]. The tremor data were collected through the piezoelectric layer, analyzed, and then mitigated using a proportional-derivative (PD) controller [58]. It was also reported that increasing the controller gain and piezoelectric constant can improve the efficiency of the attenuator.…”
Section: Active Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…They provide sensing and actuating features, which make them appropriate materials for vibration control. PZT transducers have been widely used as sensors and actuators in active vibration control (AVC) systems owing to their special properties [ 9 , 10 , 11 , 12 , 13 ]. PZT transducers have been used in various shapes and forms, such as perfectly bounded layers along surfaces of structures or patches in different sizes.…”
Section: Introductionmentioning
confidence: 99%